Ceramide-C16 Is a Versatile Modulator of Phosphatidylethanolamine Polymorphism - Doroudgar, Mahmoudreza (Biophys J, 2017)
Ceramide-C16 (CerC16) is a sphingolipid associated with several diseases like diabetes, obesity, Parkinson disease, and certain types of cancers. As a consequence, research efforts are devoted to identify the impact of CerC16 on the behavior of membranes, and to understand how it is involved in these diseases. In this work, we investigated the impacts of CerC16 (up to 20 mol %) on the lipid polymorphism of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE), using differential scanning calorimetry, and sequential (2)H and (31)P solid-state nuclear magnetic resonance spectroscopy. A partial phase diagram is proposed. The results indicate that the presence of CerC16 leads to an upshift of the temperature of the gel-to-liquid crystalline (L(β) − L(α)) phase transition, leading to a large L(β)/L(α) phase coexistence region where gel-phase domains contain ∼35 mol % CerC16. It also leads to a downshift of the temperature of the lamellar-to-inverted hexagonal (L − H(II)) phase transition of POPE. The opposite influence on the two-phase transitions of POPE brings a three-phase coexistence line when the two transitions overlap. The resulting H(II) phase can be ceramide enriched, coexisting with a L(α) phase, or ceramide depleted, coexisting with a L(β) phase, depending on the CerC16 proportions. The uncommon capability of CerC16 to modulate the membrane fluidity, its curvature propensity, and the membrane interface properties highlights its potential as a versatile messenger in cell membrane events.